The comparison of the lifestyle of vaccinated versus unvaccinated elite athletes during the Covid-19 pandemic: A multi-country comparison - Mahdi Ashouri; morteza taheri; khadijeh irandoust; Masoud Mirmoezzi (Sport Sciences and Health Research)
Background: The COVID-19 pandemic has resulted in global home confinement and quarantine, leading to the vaccination of societies worldwide. However, some elite athletes have negative views toward vaccination.Aim: This study aimed to compare the lifestyle of vaccinated versus unvaccinated international elite athletes during the COVID-19 pandemic.Materials and Methods: From March to October 2021, an online survey was conducted, including socio-individual information of athletes, the International Physical Activity Questionnaire (IPAQ), the Rapid Eating Assessment for Participants (REAP-S), and the Petersburg Sleep Quality Questionnaire (PSQI). A total of 581 elite athletes from 4 continents (Europe, Asia, Africa, and America) and different countries, aged 18-35 years, were voluntarily recruited. Data analysis was performed using U-Mann-Whitney and Wilcoxon signed-rank tests, with the level of significance set at alpha P<0.05.Results: The results indicated that there was a significant difference between the level of physical activity and eating behavior of vaccinated versus unvaccinated elite athletes (P<0.001). However, no significant difference was found between the quality of sleep among vaccinated and unvaccinated elite athletes (P=0.270).Conclusion: It was shown that, despite the unvaccinated status of some elite athletes (49.9%), their physical activity levels were higher than those of vaccinated elite athletes during the COVID-19 pandemic. Additionally, the eating behavior of vaccinated elite athletes was better than that of unvaccinated elite athletes during the COVID-19 pandemic, but there was no significant difference in the quality of sleep between the groups.